OsVIL2 Regulates Spikelet Development by Controlling Regulatory Genes in Oryza sativa - Yoon, Hyeryung; Yang, Jungil; Liang, Wanqi; Zhang, Dabing; An, Gynheung (Frontiers in Plant Science, 2018)
Flower organ patterning is accomplished by spatial and temporal functioning of various regulatory genes. We previously reported that Oryza sativa VIN3-LIKE 2 (OsVIL2) induces flowering by mediating the trimethylation of Histone H3 on LFL1 chromatin. In this study, we report that OsVIL2 also plays crucial roles during spikelet development. Two independent lines of T-DNA insertional mutants in the gene displayed altered organ numbers and abnormal morphology in all spikelet organs. Scanning electron microscopy showed that osvil2 affected organ primordia formation during early spikelet development. Expression analysis revealed that OsVIL2 is expressed in all stages of the spikelet developmental. Transcriptome analysis of developing spikelets revealed that several regulatory genes involved in that process and the formation of floral organs were down-regulated in osvil2. These results suggest that OsVIL2 is required for proper expression of the regulatory genes that control floral organ number and morphology.